The Virtual Infernal: Philippe de Loutherbourg, William Beckford and the Spectacle of the Sublime - McCalman, Iain (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractIn the autumn of 1781, shortly after being elected to the British Academy of Art as a landscape painter, Alsatian-born artist Philippe Jacques de Loutherbourg was hired by the wealthy young aesthete William Beckford to prepare a private birthday spectacle at his mansion in Wiltshire. De Loutherbourg, who was also chief scenographer at Drury Lane theatre and the inventor of a recent commercial “moving picture” entertainment called the Eidophusikon, promised to produce “a mysterious something that the eye has not seen nor the heart conceived.” Beckford wanted an Oriental spectacle that would completely ravish the senses of his guests, not least so that he could enjoy a sexual tryst with a thirteen year old boy, William Courtenay, and Louisa Beckford, his own cousin’s wife.The resulting three day party and spectacle staged over Christmas 1781 became one of the scandals of the day, and ultimately forced William Beckford into decades of exile in Europe to escape accusations of sodomy. However, this Oriental spectacle also had a special significance for the history of Romantic aesthetics and modern-day cinema. Loutherbourg and Beckford’s collaboration provided the inspiration for William to write his scintillating Gothic novel, Vathek, and impelled Philippe himself into revising his moving-picture program in dramatically new ways. Ultimately this saturnalian party of Christmas 1781 constituted a pioneering experiment in applying the aesthetic of the sublime to virtual reality technology. It also led Loutherbourg to anticipate the famous nineteenth-century “Phantasmagoria” of French showman, Gaspard Robertson, by producing in 1782 a miniature Gothic movie scene based on the Pandemonium episode in Milton’s Paradise Lost.